Men's access to primary health care services: an integrative review (Research, Society and Development, 2020)
To analyze the access of men to primary health care services from the perspective of nursing. This is an integrative literature review based on the selection of articles in the BDENF, LILACS and SciELO databases. As inclusion criteria for the selection of the sample were used: original articles, published in Portuguese and between 2014 and 2018. Therefore, 21 articles were selected for analysis, interpretation, discussion and structuring of this article. We grouped them for discussion in the following categories: the absence of men in the primary health service from the male perspective; nursing and men's access to primary health care services; and strategies used in primary health care to facilitate men's access to health services. There were weaknesses regarding nursing performance in guaranteeing access to men in primary health care services, namely: lack of knowledge about the national policy of integral attention to men's health, lack of training and lack of training adoption of effective strategies capable of meeting men's health needs.